1998
DOI: 10.1093/emboj/17.7.2055
|View full text |Cite
|
Sign up to set email alerts
|

Hus1p, a conserved fission yeast checkpoint protein, interacts with Rad1p and is phosphorylated in response to DNA damage

Abstract: The hus1+ gene is one of six fission yeast genes, termed the checkpoint rad genes, which are essential for both the S-M and DNA damage checkpoints. Classical genetics suggests that these genes are required for activation of the PI-3 kinase-related (PIK-R) protein, Rad3p. Using a dominant negative allele of hus1+, we have demonstrated a genetic interaction between hus1+ and another checkpoint rad gene, rad1+. Hus1p and Rad1p form a stable complex in wild-type fission yeast, and the formation of this complex is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
123
2
2

Year Published

1998
1998
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(134 citation statements)
references
References 67 publications
7
123
2
2
Order By: Relevance
“…hRad1, hRad9, and hHus1 Associate in a Checkpoint Complex-Comparisons of the predicted human and yeast protein sequences indicate that the human proteins are 25-30% identical and 53-57% similar to their respective homologs, with homologies extending over extensive portions of each protein (12)(13)(14)(15)(16)(17)(18). In S. pombe, spRad1 and spHus1 associate in wildtype, but not rad9, mutant yeast.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…hRad1, hRad9, and hHus1 Associate in a Checkpoint Complex-Comparisons of the predicted human and yeast protein sequences indicate that the human proteins are 25-30% identical and 53-57% similar to their respective homologs, with homologies extending over extensive portions of each protein (12)(13)(14)(15)(16)(17)(18). In S. pombe, spRad1 and spHus1 associate in wildtype, but not rad9, mutant yeast.…”
Section: Resultsmentioning
confidence: 99%
“…In S. pombe, spRad1 and spHus1 associate in wildtype, but not rad9, mutant yeast. One interpretation of this result is that spRad9 may physically link spRad1 to spHus1, although this hypothesis has not been validated experimentally (18). To address whether conservation extends to a functional level, we examined the ability of the human homologs to form biochemical complexes similar to those reported in yeast.…”
Section: Resultsmentioning
confidence: 99%
“…Rad9 forms a complex with Hus1 and Rad1 and is itself phosphorylated in response to DNA damage. Both of these post-translational modification events are dependent on the remaining checkpoint Rad proteins but independent of Crb2 (also termed Rhp9) and the effector kinases (Kostrub et al, 1998;Caspari et al, 2000a;Caspari et al, 2000b). Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins are fundamental to both pathways and appear necessary for the receipt and transmission of the checkpoint signal (Al-Khodairy and Carr, 1992;Enoch et al, 1992;O'Connell et al, 2000). As yet, the precise mechanism(s) by which these proteins act to achieve this goal is unclear, although recent studies have indicated the presence of discrete intracellular complexes between Rad3 and Rad26, between Rad17 and the four small subunits of replication factor C (RFC) and between Rad9, Rad1 and Hus1 (Edwards et al, 1999;Shimada et al, 1999;Kostrub et al, 1998;Caspari et al, 2000a). The Rad3-Rad26 complex functions as a PI3-related protein kinase and the Rad1-dependent complex (known as the 9-1-1 complex) is related to the proliferating cell nuclear antigen (PCNA) sliding clamp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation